1999
DOI: 10.1074/jbc.274.25.17612
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Protects Epithelial Cells against Fas-induced Apoptosis

Abstract: Chemotherapeutic drugs that damage DNA kill tumor cells, in part, by inducing the expression of a death receptor such as Fas or its ligand, FasL. Here, we demonstrate that epidermal growth factor (EGF) stimulation of T47D breast adenocarcinoma and embryonic kidney epithelial (HEK293) cells protects these cells from Fas-induced apoptosis. EGF stimulation of epithelial cells also inhibited Fas-induced caspase activation and the proteolysis of signaling proteins downstream of the EGF receptor, Cbl and Akt/protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(155 citation statements)
references
References 39 publications
9
145
1
Order By: Relevance
“…Apoptosis has also been proven to be prominently increased in EGFR anti-sense-or siRNA-treated groups, indicating that EGFR is an important way to induce the cascade-dependent apoptosis (Schaerli and Jaggi, 1998;Gibson et al, 1999;Lage et al, 2003;Kang et al, 2006). Our study discovered several novel concepts for biological therapy.…”
Section: Discussionsupporting
confidence: 52%
“…Apoptosis has also been proven to be prominently increased in EGFR anti-sense-or siRNA-treated groups, indicating that EGFR is an important way to induce the cascade-dependent apoptosis (Schaerli and Jaggi, 1998;Gibson et al, 1999;Lage et al, 2003;Kang et al, 2006). Our study discovered several novel concepts for biological therapy.…”
Section: Discussionsupporting
confidence: 52%
“…Increased EGFR phosphorylation in cancer cells following exposure to cytotoxic drugs has been shown in other studies (Koizumi et al, 2004), and the activation of EGFR could constitute a pro-survival response. Furthermore, a number of reports have suggested that EGFR promotes cell survival and protects cells from death-receptor-mediated apoptosis through the activation of AKT pathway (Gibson et al, 1999). Our results suggest that the nature of the synergistic interaction between PP2 and 5-FU and the observed chemo-sensitizing effect is most likely associated with the inhibition of EGFR-AKT intracellular pathway by PP2.…”
Section: Discussionsupporting
confidence: 50%
“…Here, we used the T47D human breast cancer cell line, which is a model system for studies of PRL and EGF action in breast cancer biology (Das and Vonderhaar, 1996a, b;Haraguchi et al, 1997;Gibson et al, 1999;Maus et al, 1999;Badache and Hynes, 2001;Lichtner et al, 2001;Chen et al, 2002;Chughtai et al, 2002;Kassenbrock et al, 2002;Acosta et al, 2003). We first tested responsiveness to each stimulus in these cells.…”
Section: Prl Promotes Erk-dependent Threonine Phosphorylation Of Egfrmentioning
confidence: 99%